Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Hydrogeochemistry and quality of surface water and groundwater in the vicinity of Lake Monoun, West Cameroon: approach from multivariate statistical analysis and stable isotopic characterization - Brice T. Kamtchueng; Wilson Y. Fantong; Mengnjo J. Wirmvem; Rosine E. Tiodjio; Alain F. Takounjou; Jules R. Ndam Ngoupayou; Minoru Kusakabe; Jing Zhang; Takeshi Ohba; Gregory Tanyileke; Joseph V. Hell; Akira Ueda (Environmental Monitoring and Assessment, 2016)

Biological index of environmental lead pollution: accumulation of lead in liver and kidney in mice - T. Takano; Y. Okutomi; M. Mochizuki; Y. Ochiai; F. Yamada; M. Mori; F. Ueda (Environmental Monitoring and Assessment, 2015)

Revision of Begomovirus taxonomy based on pairwise sequence comparisons - Judith K. Brown; F. Murilo Zerbini; Jesús Navas-Castillo; Enrique Moriones; Roberto Ramos-Sobrinho; José C. F. Silva; Elvira Fiallo-Olivé; Rob W. Briddon; Cecilia Hernández-Zepeda; Ali Idris; V. G. Malathi; Darren P. Martin; et al. (Archives of Virology, 2015)

Characterization of a new anulavirus isolated from Amazon lily plants - S. Fuji; M. Kikuchi; S. Ueda; T. Toda; H. Furuya; F. Fukumoto; K. Hanada (Archives of Virology, 2013)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Complete nucleotide sequences of attenuated and severe isolates of Leek yellow stripe virus from garlic in northern Japan: Identification of three distinct virus types in garlic and leek world-wide - F. Takaki; T. Sano; K. Yamashita; T. Fujita; K. Ueda; T. Kato (Archives of Virology, 2005)

Development and disintegration of phragmoplasts in living cultured cells of a GFP?TUA6 transgenic Arabidopsis thaliana plant - K. Ueda; S. Sakaguchi; F. Kumagai; S. Hasezawa; H. Quader; U. Kristen (Protoplasma, 2003)

Slight difference in primary amino acid sequence of p17 matrix protein of HIV-1 exerts profound influence on its antigenicity - K. Taniguchi; H. Tsuchie; S. Kageyama; M. Iwasaki; T. Takagi; F. Sasao; S. Ueda; T. Kurimura (Archives of Virology, 1998)